2004
DOI: 10.1097/00003727-200407000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Emergency Preparedness Training Program for Public Health Nurses in New York City

Abstract: A public health workforce that is competent to respond to emergencies is extremely important. We report on the impact of a training program designed to prepare public health nurses to respond appropriately to emergencies. The program focused on the basic public health emergency preparedness competencies and the emergency response role of public health workers employed by the New York City School Department of Health and Mental Hygiene School Health Program. The evaluation methods included pre/post-testing foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
51
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 3 publications
6
51
0
1
Order By: Relevance
“…Their findings showed that mean score of knowledge, attitude, and performance of nurses after the intervention significantly increased which was consistent with the present study [19]. Borhan Nezhad (2010) also in an interventional study investigated the effect of implementing hospital incident command system on preparedness of Incidents and Disasters Committee on Zarand nursing staff.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Their findings showed that mean score of knowledge, attitude, and performance of nurses after the intervention significantly increased which was consistent with the present study [19]. Borhan Nezhad (2010) also in an interventional study investigated the effect of implementing hospital incident command system on preparedness of Incidents and Disasters Committee on Zarand nursing staff.…”
Section: Discussionsupporting
confidence: 89%
“…Implementation of educational programs on reducing mortality of the injured during disasters has been effective, because it leads to promotion of staff awareness about existing programs to cope with the incidents and disasters, increasing their participation in planning and solving existing problems, and improving staff skills in carrying out their assigned tasks [19].…”
Section: Discussionmentioning
confidence: 99%
“…As was previously noted, approximately 40% of healthcare workers said that they would not attend work if biologically contaminated patients were in the hospital (Hanfling 2005, Masterson et al 2008, and over 50% said they would not report to work during a SARS epidemic (Qureshi et al 2004). Granted, the survey participants were American healthcare workers, whereas the healthcare workers responding to SARS were Canadian.…”
mentioning
confidence: 91%
“…However, the evidence base for evaluation of public health workforce training efforts is relatively small, though it continues to expand. Evaluations have been conducted on a range of public health training activities, including examinations of the impacts of evidence-based practices on individual skills (4, 5), trainings on disaster preparedness and response skills (6), leadership skills for upper-tier managers (7), community based participatory approaches to training (8), online and distance education-based training (9, 10), and satisfaction with formal Masterā€™s in Public Health programs (11, 12). Public health researchers, practitioners, and program sponsors hope that continuing evaluation efforts will shed light on organizational capacity, service delivery, and, ultimately, consumer and public health outcomes (1, 13).…”
Section: Introductionmentioning
confidence: 99%